Far-infrared elastic scattering proposal for the Avogadro Project's silicon spheres. (May 2018) - Humayun, Muhammad Hamza; Khan, Imran; Azeem, Farhan; Chaudhry, Muhammad Rehan; Gökay, Ulaş Sabahattin; Murib, Mohammed Sharif; Serpengüzel, Ali
Highlights: Far-IR spectroscopy for determining the Avogadro constant by using elastic scattering from the 100 mm silicon spheres is proposed. Near-IR spectroscopy already relates WGMs of the 1 mm silicon spheres diameter of the spheres. Numerical simulations in the far-IR and the near-IR are presented. Spatially scaled down elastic scattering measurements in the near-IR are presented. Diameter measurements of 100 mm silicon spheres with elastic scattering in the far-IR can be an alternative method. Abstract: Avogadro constant determines the number of particles in one mole of a substance, thus relating the molar mass of the substance to the mass of this substance. Avogadro constant is related to Système Internationale base units by defining the very concept of chemical quantity. Revisions of the base units created a need to redefine the Avogadro constant, where a collaborative work called the Avogadro Project is established to employ optical interferometry to measure the diameter of high quality 100 mm silicon spheres. We propose far-infrared spectroscopy for determining the Avogadro constant by using elastic scattering from the 100 mm Avogadro Project silicon spheres. Similar spectroscopic methods are already in use in the near-infrared, relating whispering gallery modes of the 1 mm silicon spheres to the diameter of the spheres. We present numerical simulations in the far-infrared and the near-infrared, as well as spatially scaled down elastic scattering measurements in the near-infrared. These numerical and experimental results show that, the diameter measurements of 100 mm single crystal silicon spheres with elastic scattering in the far-infrared can be considered as an alternative to optical interferometry.